Dynamic stress state around shallow-buried cavity under transient P wave loads in different conditions. (March 2020) - Li, Zhanwen; Tao, Ming; Du, Kun; Cao, Wenzhuo; Wu, Chengqing
Highlights: The theoretical model of cavity under various transient P wave loads is obtained. Stress distributions around cavity of high and low frequency loads are different. Waveform and burial depth affect the stress amplitude around cavity. Convergence of solutions are investigated. The existence of linear boundary increases the risk of tensile failure around cavity. Abstract: The failure of underground structure is always caused by local stress redistribution resulted from transient impact loads. An analytical model is established and solved by using the complex variable function method to illustrate the dynamic stress concentration around a shallow-buried cavity under transient P wave loads. The transient wave response is attained as an integration of steady-state wave response in circular frequency domain. By adopting a Butterworth filter, the jump points in the dynamic stress concentration factor (DSCF) curve which is not in line with the overall trend is filtered out to obtain more reasonable results. The convergence and accuracy of the solutions are verified and discussed in detail. DSCF distributions of high wavenumber incidences differ from that of low wavenumber incidences significantly in amplitudes and distribution patterns. The effects of the cavity depth, incidence angle and position of wave peak on DSCF distributions are illustrated.